Kajian fenomena "No-Show Phenomenon" dalam kalangan calon yang telah ditawarkan kemasukan ke USM. - Abd Razak, Nordin (Universiti Sains Malaysia, 2017)

(untitled)
Like any other business institution, a higher education institution such as Universiti Sains Malaysia (USM) needs to understand its customer needs and wants in order to remain competitive and survive among higher education providers. This is also important in order to attract and retain the potential candidates to pursue (MOHE) in 2009, USM has a privilege to screen and select potential students to continuing their studies at the undergraduate level.